2009
DOI: 10.1007/s00383-008-2317-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life: urinary bladder augmentation or substitution in children

Abstract: Bladder augmentation or substitution significantly improved the health-related quality of life in children and young adolescents taking part in the study. The authors are planning a prospective long-term follow-up of the patients (longitudinal study) to validate the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
(18 reference statements)
1
24
2
4
Order By: Relevance
“…Many of the studies reporting QOL in bladder exstrophy are limited in that they are retrospective studies, use nonvalidated or physician directed questionnaires, and have small sample sizes. 10,11 Wittmeyer et al recently used the generic SF-36 to assess 25 French adult patients with exstrophy, and found their QOL scores lower than the norms in general health perception and physical activity, but otherwise comparable to those of normal adults. 12 In a second study using the SF-36 Jochault-Ritz et al found French adolescent patients with exstrophy to have superior QOL scores compared to adult and child patients with exstrophy as well as the general population.…”
mentioning
confidence: 99%
“…Many of the studies reporting QOL in bladder exstrophy are limited in that they are retrospective studies, use nonvalidated or physician directed questionnaires, and have small sample sizes. 10,11 Wittmeyer et al recently used the generic SF-36 to assess 25 French adult patients with exstrophy, and found their QOL scores lower than the norms in general health perception and physical activity, but otherwise comparable to those of normal adults. 12 In a second study using the SF-36 Jochault-Ritz et al found French adolescent patients with exstrophy to have superior QOL scores compared to adult and child patients with exstrophy as well as the general population.…”
mentioning
confidence: 99%
“…Bladder augmentation is believed to improve the quality of life of children or adolescents with urinary incontinence 10 . The closure of the bladder neck performed during ileocystoplasty is effective for the control of urinary incontinence.…”
Section: Resultsmentioning
confidence: 99%
“…It provides a low-pressure, continent, catheterisable reservoir for urine, protects the upper tracts, markedly improves continence and enhances quality of life [1]. Urolithiasis is a complication of BA, with lifelong risk.…”
Section: Introductionmentioning
confidence: 99%